PENERAPAN MEDIA AUDIO CERITA RAKYAT LOKAL MAGETAN UNTUK MENUMBUHKAN NILAI RELIGIUS DALAM PEMBELAJARAN BAHASA INDONESIA SISWA KELAS V - Heny Kusuma Widyaningrum (MUADDIB Jurnal Kependidikan dan Keislaman, 2018)
The objectives of this study are to (1) plan teaching learning Indonesian with media audio of local folklore of Magetan to cultivate religious values in MI Nurul Islam Tanjung Bendo, Magetan, (2) do teaching learning Indonesian with media audio of local folklore of Magetan to cultivate religious values in MI Nurul Islam Tanjung Bendo, Magetan, and (3) evaluate teaching learning Indonesian with media audio of local folklore of Magetan to cultivate religious values in MI Nurul Islam Tanjung Bendo, Magetan.  This research using qualitative research descriptive. Source of the data in this study are both learning activities conducted by the teachers and students, and documentation. Techniques collecting data used was interviewing and documentating. The results showed that (1) planning of teaching learning is in the form of lesson plan (RPP) and the preparation of the media audio is in the form of recording, and also the tests (2) teaching learning Indonesian is based on the lesson plans, settig up a teaching materials and software learning. (3) evaluating the teachig learning was done in the form of written and oral test.